Poly-l-gamma-glutamic acid production by recombinant Bacillus subtilis without pgsA gene - Kazuhisa Sawada; Hiroyuki Araki; Yasushi Takimura; Kenta Masuda; Yasushi Kageyama; Katsuya Ozaki; Hiroshi Hagihara (AMB Express, 2018)
Abstract Poly-gamma-glutamic acid (PGA) is a promising bio-based polymer that shares many functions with poly (acrylic acid) and its derivatives. Thus, technologies for efficient production and molecular size control of PGA are required to expand the application of this useful biopolymer. In Bacillus strains, PGA is synthesized by the PgsBCA protein complex, which is encoded by the pgsBCA gene operon, otherwise is known as ywsC and ywtAB operons and/or capBCA operon. Hence, we investigated responsible components of the PgsBCA complex in B. subtilis for over-production of PGA. In particular, we constructed genomic pgsBCA gene-deletion mutants of B. subtilis. And also, we assembled high copy-number plasmids harboring σA-dependent promoter, leading to high-level expression of all combinations of pgsBCA, pgsBC, pgsBA, pgsCA, pgsB, pgsC, and/or pgsA genes. Subsequently, PGA production of the transformed B. subtilis mutant was determined in batch fermentation using medium supplemented with l-glutamate. PGA production by the transformants introduced with pgsBC genes (lacking the genomic pgsBCA genes) was 26.0 ± 3.0 g L−1, and the enantiomeric ratio of d- and l-glutamic acid (d/l-ratio) in the produced PGA was 5/95. In contrast, d/l-ratio of produced PGA by the transformants introduced with pgsBCA genes (control strains) was 75/25. In conclusion, B. subtilis without pgsA gene could over-produce PGA with an l-rich enantiomeric ratio.